Biodiversity across trophic levels drives multifunctionality in highly diverse forests - Schuldt, Andreas; Assmann, Thorsten; Brezzi, Matteo; Buscot, François; Eichenberg, David; Gutknecht, Jessica; Härdtle, Werner; He, Jin-Sheng; Klein, Alexandra-Maria; Kühn, Peter; Liu, Xiaojuan; Ma, Keping; et al. (Nature communications, 2018)
Human-induced biodiversity change impairs ecosystem functions crucial to human well-being. However, the consequences of this change for ecosystem multifunctionality are poorly understood beyond effects of plant species loss, particularly in regions with high biodiversity across trophic levels. Here we adopt a multitrophic perspective to analyze how biodiversity affects multifunctionality in biodiverse subtropical forests. We consider 22 independent measurements of nine ecosystem functions central to energy and nutrient flow across trophic levels. We find that individual functions and multifunctionality are more strongly affected by the diversity of heterotrophs promoting decomposition and nutrient cycling, and by plant functional-trait diversity and composition, than by tree species richness. Moreover, cascading effects of higher trophic-level diversity on functions originating from lower trophic-level processes highlight that multitrophic biodiversity is key to understanding drivers of multifunctionality. A broader perspective on biodiversity-multifunctionality relationships is crucial for sustainable ecosystem management in light of non-random species loss and intensified biotic disturbances under future environmental change. Biodiversity change can impact ecosystem functioning, though this is primarily studied at lower trophic levels. Here, Schuldt et al. find that biodiversity components other than tree species richness are particularly important, and higher trophic level diversity plays a role in multifunctionality.